Amorphous HKUST-1 Nanoparticles and Their Modification for Highly Sensitive Dengue Virus Immunosensor. Issue 9 (27th September 2022) - Dewi, Kariana Kusuma; Septiani, Ni Luh Wulan; Nugraha, N; Natalia, Dessy; Yuliarto, Brian
Abstract : In this work, the amorphous HKUST-1 nanoparticles (aHKUST1) and copper hydroxide nanosheet (Cu(OH)2 NS) were successfully prepared by involving diethanolamine (DEOA) and were applied as an immunosensor to detect dengue virus (DENV-3) NS1. 35 wt% of DEOA was found to not only provide a base environment but also act as a crystal modifier for the HKUST-1. The DEOA changes the crystallinity and morphology of HKUST-1 into amorphous and highly uniform nanoparticles, respectively. In addition, the Cu(OH)2 NS was obtained by immersing the aHKUST1 NPs in water for 6 h. The aHKUST1 NPs and Cu(OH)2 NS were functionalized as a matrix material to immobilize the DENV-3 monoclonal antibody. The immunosensor was fabricated by dropping the matrix on the surface of a screen-printed carbon electrode (SPCE). The immunosensor performances were evaluated by cyclic voltammetry (CV), differential pulse voltammetry (DPV), and electrochemical impedance spectroscopy (EIS) technique in detecting DENV-3 NS1 antigen at the concentration in the range of 0.001–100 ng ml −1 . As immunosensor aHKUST1 NPs and Cu(OH)2 NS can detect the antigen down to 1.64 pg ml −1 and 2.07 pg ml −1, respectively. The amorphous nature of HKUST-1 is believed to provide many active sites that can enhance electrocatalytic activities thereby improving immunosensor performance.